Kosmoteologi Islam Indonesia - Umam, Muchammad Helmi (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2012)
Environmental issues are critical questions about what will happen to the Earth in the future. Critical, because everyone agrees that humans? behavior is bad implications for the future of the earth. Evils caused by obsession and ambition of development, deterioration due to residues of rationality and technology development, to the harmful effects of the practice of politics and the state. Although not considered to contribute directly, religious people are called and aware as people who share the responsibility of the crucial questions about the environment. Is the religion concerned with the environment, whether religion actually indifferent and become part of the destroyers of the environment? This is the urgency of reviewing the issue of Islamic Cosmo-theology as a new epistemological dimension of divinity juxtaposing religion with the study of the universe.